OPERATION ZENI TNI-AD IN FACING BIOLOGICAL THREATS DURING THE COVID-19 PANDEMIC AS A STRATEGY TO STRENGTHEN THE COUNTRY'S DEFENSE - Wahyudi Adrian; Pujo Widodo; Halkis Halkis (CV. AFDIFAL MAJU BERKAH, 2023)
The involvement of the military defense function in the face of non-military threats is indirect and prioritizes the deterrence function. But on a certain scale, military defense can be engaged in a more concrete form on the basis of government political decisions or at the request of the main non-military elements that need it, for example in overcoming widespread disease outbreaks and in overcoming the impact of natural disasters or search and rescue (SAR). The worldwide Covid-19 pandemic is a form of Nubika threat that is not clear about the causative factor, but has a tremendous impact, and has increased awareness and awareness of the world community, including Indonesia, about how terrible and tragic nubika's danger is to the safety of the nation and country, even the world. The Covid-19 pandemic until 2021 is not over and the emergence of new variants has caused the spread of the virus to be faster and wider in various countries. The Indonesian government continues to strive to reduce the rate of virus transmission through various social restriction policies, including involving the TNI in assisting in handling the Covid-19 pandemic. One of them is the involvement of the Pusziad Army Explosives Taming Zeni Company (Kizi Nubika) as the only strategic unit in the Indonesian Army that specifically addresses the dangers of Nubika The biological threat can be an asymmetric war and is a major threat to human, animal, and plant health. Infectious diseases and harmful biological materials can spread and have a detrimental impact on ecosystems and economies. The Indonesian Army (Army) is expected to become a major force in dealing with biological threats through the development of capabilities and capabilities in the field of bioskills, including understanding of zoonoses, epidemiology, early detection, prevention, control, and recovery from biological threats. The Indonesian Army is also expected to cooperate with various parties, including governments, international organizations, and the scientific community, in efforts to control biological threats